A high-doped phosphogypsum-based cementing material from a solid waste source and self-grown twin seeds and a preparation method thereof
Patent Information
- Application Number
- CN202611004560.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-13
AI Technical Summary
[0010]综上,现有磷石膏基胶凝材料和全固废胶凝材料仍存在以下不足:(1)磷石膏多作为硫酸盐调节组分或填充组分使用,75%以上高掺量磷石膏作为主体胶凝组分时,体系硅铝供给不足、早期反应慢、后期结构致密化不足;(2)磷石膏在常规干燥和粉磨过程中易发生脱水转晶,影响硫酸盐稳定释放和AFt可控生成;(3)电石渣、钢渣等碱性固废在普通粉磨或碳化过程中易出现表面失活、过度碳酸盐化和后续激发能力下降;(4)现有CO2矿化和碳化固废技术多以提高固碳量或制品整体碳酸盐化为目标,未形成服务于高掺量磷石膏胶凝体系的“表层成核-内部保碱”微碳化激发结构;(5)现有全固废体系多依赖普通碱激发和配比优化,尚未建立兼具AFt有序生成、C-(A)-S-H凝胶网络构筑、纳米CaCO3异相成核和磷氟原位稳定的连续调控路线
(1)本发明以磷石膏作为主体组分,区别于将磷石膏仅作为少量硫酸盐调节组分或填料的常规路线,可显著提高磷石膏在胶凝材料中的消纳比例。
Smart Images

Figure CN122897653A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of solid waste resource utilization and low-carbon cementitious materials, specifically relating to a high-content phosphogypsum-based cementitious material made entirely from solid waste and its preparation method. Background Technology
[0002] Phosphogypsum is a major industrial byproduct of wet-process phosphoric acid production. Its main mineral component is calcium sulfate dihydrate, and it also contains residual acid, soluble phosphorus, fluorine, organic matter, and trace amounts of heavy metals. With the continuous expansion of the phosphorus chemical industry, environmental problems such as land occupation due to long-term phosphogypsum storage, leachate migration, dust diffusion, and the release of acidic components are becoming increasingly prominent. Although phosphogypsum can participate in gelation reactions as a sulfate source, its silicon and aluminum content is insufficient, making it difficult to form a stable and continuous gelation network when used alone. It usually needs to be co-utilized with granulated blast furnace slag, fly ash, carbide slag, steel slag, and other solid wastes. Existing research shows that the phosphogypsum-slag-fly ash-carbide slag system can improve strength through the synergistic formation of AFt and C-(A)-SH gels. However, high-dosage phosphogypsum systems still suffer from insufficient silicon and aluminum release, slow early-stage reactions, disordered growth of ettringite, insufficient volume stability, and inadequate phosphorus and fluorine stabilization.
[0003] Currently, the technology for the resource utilization of phosphogypsum mainly focuses on backfill materials, cementitious materials, recycled aggregates, and building materials. Existing technologies propose to construct a complete solid waste backfill system with phosphogypsum, slag, carbide slag, iron ore tailings, or fly ash, and improve the backfilling coverage and strength through proportion optimization (CN110723952B). However, the phosphogypsum content in these technologies is mostly 40% to 65%, which is more inclined towards the proportion optimization of mine backfill materials. The problems of crystal phase protection, silicon-aluminum compensation, crystal seeding, and phosphorus-fluorine stabilization when phosphogypsum with a high content of more than 75% is used as the main cementitious component have not yet been solved. Another technology uses phosphogypsum, slag powder, yellow phosphorus slag, bentonite, attapulgite powder, carbide slag, nano-silicon-based powder, PAN carbon fiber, sodium alginate, and SAP high-expansion resin to prepare modified phosphogypsum-based reinforced and toughened cementitious materials (CN114149187B). Although this method can improve the toughness and crack resistance of the material, it introduces functional components from non-solid waste sources, and the technology focuses on reinforcement and toughening and applications in roads and block products, without forming a fully solid waste-derived seed crystal activation system.
[0004] Regarding the modification of phosphogypsum cementitious materials, existing technologies have proposed using anhydrous phosphogypsum as the main component, combined with siliceous aluminate solid waste slurry, alkaline solid waste, and water-reducing agents, to prepare highly water-resistant anhydrous phosphogypsum cementitious materials (CN111978061B). This technology emphasizes improving the water resistance of anhydrous phosphogypsum through wet milling of siliceous aluminate solid waste, but it focuses on anhydrous phosphogypsum and does not involve temperature-controlled crystal-preserving drying of the CaSO4·2H2O phosphogypsum crystal phase, nor does it propose fractional temperature-limited ultrafine activation with D90≤10 μm, self-generation of AFt / C-(A)-SH twin seeds from all solid waste sources, or CO2 micro-carbonization nucleation technology. Another technology for recycled aggregates based on phosphogypsum and other solid wastes prepares recycled aggregates from phosphogypsum, fly ash, steel slag, etc. (CN119954477A). Its core lies in the formation of aggregate structure and the improvement of recycled aggregate performance. The product form is different from the high-dosage phosphogypsum-based cementitious material described in this invention, and it does not solve the problems of early activation and twin seed induction in the high-dosage phosphogypsum cementitious system.
[0005] In the field of all-solid-waste cementitious materials, existing technologies have been developed to prepare self-activated alkaline cementitious materials using solid wastes such as red mud, carbide slag, desulfurized gypsum, fly ash, and slag as raw materials (CN115925299A). This technology utilizes red mud and carbide slag to provide an alkaline environment, desulfurized gypsum to provide sulfates, and fly ash and slag to provide active substances. All solid wastes are ball-milled and sieved before use, representing a typical route for alkaline solid waste self-activated cementitious materials. However, this technology uses desulfurized gypsum as the sulfate component, rather than high-dosage phosphogypsum as the main component, and does not propose specific control measures for stabilizing phosphorus and fluorine impurities in phosphogypsum and protecting the crystal phase of dihydrate gypsum. Its grinding control is mainly based on sieving and specific surface area, without considering the differences in crystal phase, alkalinity, and activity of different solid wastes such as phosphogypsum, carbide slag, slag, and fly ash for separate, temperature-limited ultrafine activation. Another solid waste-based cementitious material technology uses raw materials such as steel slag, carbide slag, gypsum, slag, red mud, and fly ash, and improves the powder reactivity through interface modifiers and stepwise grinding (CN119822776B). This technology preferentially uses desulfurized gypsum, and reduces the powder surface energy, prevents agglomeration, and improves grinding efficiency and hydration activity through interface modifiers. Although this method involves solid waste-based cementitious materials and grinding activation, its core technology lies in interface modifier-assisted grinding and multi-solid waste compounding. It does not propose a high-dosage system with 75-88 parts of phosphogypsum as the main component, nor does it disclose the continuous process of "temperature-controlled crystal-preserving drying - D90≤10 μm fractional temperature-limited ultrafine activation - fly ash-based porous carrier alkaline thermal reconstruction - self-generation of AFt / C-(A)-SH twin crystals from solid waste source - graded CO2 micro-carbonization nucleation".
[0006] In terms of powder activation, existing technologies mostly aim to increase specific surface area, reduce sieve residue, or improve grinding efficiency, typically employing ball milling, wet milling, stepwise milling, or grinding aids for control. For example, some patents for solid waste cementitious materials require raw materials to reach a certain specific surface area or sieve particle size (CN115925299A, CN119822776B), but do not separately control the grinding temperature rise, crystal phase stability, and active phase exposure based on the reaction functions of different solid wastes. For phosphogypsum, the key effective phase is CaSO4·2H2O. If the drying or grinding temperature is too high, it is easy to lose the water of crystallization and transform into hemihydrate or anhydrous gypsum, affecting sulfate release and AFt formation. For carbide slag, if the grinding temperature rise is too high or the exposure time is too long, Ca(OH)2 is prone to significant carbonization, hard agglomeration, or surface deactivation. For slag, fly ash, steel slag, and waste glass, if only ordinary grinding is used, the glass phase, calcium-silicon phase, and silicon-aluminum active phase are not sufficiently exposed, making it difficult to support the continuous strength development of high-dosage phosphogypsum systems. Therefore, ordinary grinding technology cannot simultaneously meet the requirements of phosphogypsum crystal phase protection, carbide slag alkalinity maintenance, silicon-aluminum solid waste activation, and uniform seed dispersion.
[0007] In the utilization of CO2 mineralization and carbonized solid waste, existing technologies largely focus on CO2 fixation through steel slag mineralization, carbonization curing of cement products, carbonized bricks, and carbonized lightweight aggregates. For example, existing technologies enhance the reaction between calcium oxide components in steel slag and CO2 by adding alkali metal salt catalysts to improve the CO2 fixation efficiency of steel slag mineralization (CN103111186B). Another technology uses thiourea slag, carbonized cementitious materials, compounding agents, and aggregates to prepare low-cost thiourea slag carbonized bricks, and improves the product strength and carbon fixation effect through carbonization curing (CN115108784B). Yet another technology uses biochar as a CO2 transport channel to promote internal carbonization of solid waste-based lightweight aggregates, improving carbonization efficiency and aggregate performance (CN114538850A). These technologies typically aim to increase CO2 absorption, form carbonate solids, or improve the strength of carbonized products. They often pursue a high degree of carbonization or overall carbonate formation, and have not proposed a micro-carbonization gradient structure for high-dosage phosphogypsum-based cementitious materials, which involves "nano-CaCO3 nucleation on the particle surface and retention of Ca(OH)2 / free CaO / active calcium-silicon phase inside".
[0008] For high-dosage phosphogypsum-based cementitious materials, if carbide slag or steel slag is completely carbonized, a large amount of its internal Ca(OH)2, free CaO, and active calcium-silicon phase will be consumed, leading to a decrease in the system's alkalinity, which is detrimental to the subsequent hydration reactions of slag, fly ash, and phosphogypsum. Therefore, CO2 treatment cannot simply follow the approach of steel slag carbonization or carbonized brick curing; instead, it should be controlled as a micro-carbonization nucleation process, that is, forming nano-CaCO3 nucleation sites only on the particle surface to induce uniform dispersion and secondary growth of AFt and C-(A)-SH crystal nuclei, while retaining the alkaline components inside the particles for continuous activation. Existing CO2 mineralization fixation technologies (CN103111186B), carbonized brick technologies (CN115108784B), and carbonized lightweight aggregate technologies (CN114538850A) do not disclose this type of staged CO2 micro-carbonization nucleation route serving as a dual-seed activator for all solid waste sources.
[0009] Furthermore, existing phosphogypsum-based or all-solid-waste cementitious materials often employ methods such as cement clinker, lime, water glass, sodium hydroxide, potassium hydroxide, sulfoaluminate cement, high-alumina cement, commercial CSH seed crystals, or added nanomaterials to improve early strength and shorten the reaction induction period. For example, modified phosphogypsum-based reinforced and toughened cementitious materials incorporate nano-silicon-based powders and organic polymer components (CN114149187B); high-water-resistant anhydrous phosphogypsum cementitious materials use water-reducing agents and wet-milled silica-alumina solid waste slurry (CN111978061B). While these methods can improve certain properties, they weaken the all-solid-waste properties and increase costs, carbon emissions, or the complexity of engineering applications. For large-scale engineering scenarios such as mine backfilling, grouting reinforcement, roadbed backfilling, and ecological backfilling, there is a greater need for an all-solid-waste activation route that does not rely on added commercial seed crystals and strong alkaline chemicals, yet achieves high strength and low leaching.
[0010] In summary, existing phosphogypsum-based cementitious materials and all-solid-waste cementitious materials still have the following shortcomings: (1) Phosphogypsum is mostly used as a sulfate adjusting component or filler component. When phosphogypsum with a high content of more than 75% is used as the main cementitious component, the system has insufficient silicon and aluminum supply, slow early reaction, and insufficient densification of the structure in the later stage; (2) Phosphogypsum is prone to dehydration and crystallization during conventional drying and grinding, which affects the stable release of sulfate and the controllable generation of AFt; (3) Alkaline solid wastes such as carbide slag and steel slag are prone to surface defects during ordinary grinding or carbonization. (4) Existing CO2 mineralization and carbonization solid waste technologies are mostly aimed at increasing carbon sequestration or overall carbonization of products, and have not formed a micro-carbonization activation structure of "surface nucleation-internal alkali retention" for high-dosage phosphogypsum gelation system; (5) Existing solid waste systems mostly rely on ordinary alkali activation and ratio optimization, and have not yet established a continuous regulation route that combines AFt ordered generation, C-(A)-SH gel network construction, nano-CaCO3 heterogeneous nucleation and in-situ stability of phosphorus and fluorine. Summary of the Invention
[0011] To address the limitations of phosphogypsum content in existing phosphogypsum-based cementitious materials, the easy loss of crystal water during the drying and grinding process of phosphogypsum, the difficulty in fully activating siliceous alumina solid waste through ordinary grinding, the easy carbonization and deactivation of alkaline solid wastes such as carbide slag and steel slag, and the disordered generation of AFt, insufficient formation of C-(A)-SH gel network, and the difficulty in simultaneously controlling the leaching risk of phosphorus and fluorine components in high-content phosphogypsum systems, this invention proposes a phosphogypsum-based cementitious material and its preparation method, which uses high-content phosphogypsum as the main component, takes all-solid waste-derived self-generated twin seeds as the core activation method, and takes into account strength development, volume stability, and environmental safety. This material significantly improves the content of phosphogypsum in cementitious materials and the strength of the solidified body, while simultaneously reducing the leaching risk of phosphorus, fluorine, and heavy metals. It has engineering application value in solid waste reduction, CO2 mineralization utilization, low-carbon building material preparation, mine filling, grouting reinforcement, roadbed backfilling, and ecological backfilling. It is of great significance for promoting the large-scale disposal of phosphorus chemical solid waste and the industrialization of all-solid waste low-carbon cementitious materials.
[0012] To achieve the above objectives, the technical concept of this invention is as follows: using phosphogypsum with a content of 75-88 wt% as the main component, and maintaining the CaSO4·2H2O crystal phase structure and increasing the reaction contact area through temperature-controlled drying at 35-60℃ and temperature-limited ultrafine activation with D90≤10 μm; using granulated blast furnace slag, fly ash and carbide slag to provide silicon-aluminum-calcium reaction units and alkaline environment; using aluminum ash or red mud, waste glass powder or siliceous tailings powder, carbide slag, desulfurized gypsum or phosphogypsum fine powder, steel slag micro powder and fly ash-based porous carrier as raw materials, AFt crystal nuclei and C-(A)-SH crystal nuclei are generated in situ through low-temperature hydrothermal pre-reaction; then, through CO2 micro-carbonization nucleation treatment, nano-CaCO3 heterogeneous nucleation sites are formed on the particle surface, while retaining Ca(OH)2, free CaO, active calcium-silicon phase or alkaline calcium-silicon-aluminum phase inside the particles, constructing a gradient excitation structure of "surface nucleation-internal alkali retention". Based on this, the present invention achieves synergistic control of sulfate release, silicon-aluminum dissolution, ordered growth of AFt, C-(A)-SH gel bonding, heterogeneous nucleation of nano-CaCO3 and in-situ stabilization of phosphorus and fluorine in a high-dosage phosphogypsum system, forming a low-carbon cementitious material for all solid waste suitable for mine filling, grouting reinforcement, roadbed backfilling, trench backfilling and ecological backfilling.
[0013] This invention provides a high-content phosphogypsum-based cementitious material derived from all solid waste, the composition of which is as follows by weight: 75-88 parts phosphogypsum, 6-18 parts granulated blast furnace slag, 2-8 parts fly ash, 3-8 parts carbide slag, and 0.5-3.0 parts self-generated twin seed activator derived from all solid waste; the water-cement ratio is controlled at 0.28-0.38.
[0014] According to the above scheme, the phosphogypsum, granulated blast furnace slag, fly ash, carbide slag and whole solid waste-derived bicrystalline seed activator are all subjected to ultrafine grinding and classification treatment, and the powder particle size D90≤10μm.
[0015] Specifically, the phosphogypsum is subjected to temperature-controlled drying, ball milling or vibratory milling, and air classification, resulting in a D50 of 1–5 μm and a D90 ≤ 10 μm. The drying temperature of the phosphogypsum is 35–60℃, preferably 45–55℃, and the drying time is 6–36 h to maintain the CaSO4·2H2O crystal phase structure from dehydration and transformation.
[0016] Specifically, the granulated blast furnace slag and fly ash are subjected to graded temperature-controlled drying, followed by grinding in an air jet mill, vertical mill, stirred mill, or ball mill. After grading, the D50 is 2–6 μm, the D90 is ≤10 μm, and the specific surface area is 600–1200 m². 2 / kg. The drying temperature of the granulated blast furnace slag and fly ash is 50-90℃, preferably 60-80℃, and the drying time is 4-24 h.
[0017] Specifically, after being subjected to temperature-controlled drying, grinding, and grading, the calcium carbide slag has a D50 of 1–4 μm and a D90 ≤ 10 μm. The drying temperature of the calcium carbide slag is 45–80℃, preferably 50–70℃, and the drying time is 4–24 h, in order to reduce the moisture content and avoid significant carbonization or agglomeration and deactivation of Ca(OH)2.
[0018] According to the above scheme, the preparation method of the all-solid waste-derived bicrystalline seed activator includes the following steps: (1) Preparation of pre-reaction slurry from all solid waste sources: 10-30 parts of aluminum ash or red mud with D90≤10 μm, 15-40 parts of waste glass powder or siliceous tailings powder, 20-45 parts of carbide slag, 10-25 parts of desulfurized gypsum or phosphogypsum fine powder, 5-20 parts of steel slag micro powder, and 5-20 parts of fly ash-based porous carrier are mixed by mass, and water is added and stirred to obtain pre-reaction slurry from all solid waste sources; (2) Low-temperature hydrothermal self-generated twinning seed reaction: The pre-reaction slurry is heated and hydrothermally reacted at 40-95℃ for 2-24 hours to allow Ca, Si, Al and SO4 from the solid waste source to be separated. 2- A low-temperature pre-reaction occurs, generating AFt crystal nuclei and C-(A)-SH crystal nuclei in situ, thus obtaining a self-generated twin seed precursor; (3) Graded CO2 micro-carbonization nucleation treatment: The obtained self-generated twin seed precursor product is subjected to graded CO2 micro-carbonization nucleation treatment, and the carbonization degree is controlled to be 5-35% to obtain micro-carbonized self-generated twin seed precursor. (4) Powdering treatment of activator: The obtained micro-carbonized self-generated twin seed precursor is dried at 35-80℃ for 6-36 h, and then subjected to ultrafine grinding and air classification to obtain a solid waste self-generated twin seed activator with D90≤10 μm.
[0019] According to the above scheme, the staged CO2 micro-carbonization nucleation treatment includes one or more combinations of atmospheric pressure CO2 micro-carbonization, pressurized CO2 micro-carbonization, or supercritical CO2 micro-carbonization. Specifically, the atmospheric pressure CO2 micro-carbonization treatment conditions are: CO2 volume fraction 60–99%, treatment temperature 20–60℃, treatment time 60–180 min, and solid material moisture content 5–25%. The pressurized CO2 micro-carbonization treatment conditions are: CO2 pressure 0.2–7.0 MPa, treatment temperature 20–80℃, treatment time 30–120 min, and solid material moisture content 3–25%. The supercritical CO2 micro-carbonization treatment conditions are: CO2 pressure 7.5–20 MPa, treatment temperature 35–80℃, treatment time 5–90 min, and solid material moisture content 3–25%; preferably, the CO2 pressure is 8–15 MPa, treatment temperature is 40–60℃, treatment time is 5–45 min, and solid material moisture content is 5–15%.
[0020] According to the above scheme, the preparation method of the fly ash-based porous carrier includes the following steps: Fly ash, red mud, and carbide slag were mixed in a mass ratio of (40-70):(10-30):(10-30), and water was added to adjust the water-solid ratio to 0.35-0.80. The mixture was stirred and reacted at 50-95℃ for 2-12 h. Subsequently, the mixture was dried under controlled temperature, ultrafine ground, and air classified to obtain a fly ash-based porous carrier with D90≤10 μm.
[0021] The present invention also provides a method for preparing the above-mentioned high-content phosphogypsum-based cementitious material, comprising the following steps: First, granulated blast furnace slag, fly ash, carbide slag and whole solid waste-derived twin seed activator are premixed for 3-10 minutes, then phosphogypsum is added and mixed for 3-8 minutes, and finally water is added and stirred for 3-8 minutes. The mixture is then poured, pumped, grouted or filled into shape, and cured to obtain a solidified body of high-content phosphogypsum-based cementitious material.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention uses phosphogypsum as the main component, which is different from the conventional route of using phosphogypsum only as a small amount of sulfate adjustment component or filler. It can significantly increase the proportion of phosphogypsum in cementitious materials.
[0023] (2) The present invention sets up a separate temperature-limited ultrafine activation process for different solid wastes: phosphogypsum focuses on temperature control to preserve crystals, carbide slag focuses on alkali preservation to prevent deactivation, and slag, fly ash, steel slag and waste glass powder focus on exposure of active silicon, aluminum and calcium phases, thereby improving the reaction uniformity and continuous hydration capacity of the high-dosage phosphogypsum system.
[0024] (3) The activator of this invention is entirely derived from industrial solid waste. Through alkaline thermal reconstruction of a fly ash-based porous carrier, it utilizes the pore adsorption, surface defects, and silicon-aluminum active sites to activate the Ca² released from industrial solid wastes such as carbide slag, steel slag powder, red mud, and aluminum ash. + AlO2 - SiO4 4- and OH - Interfacial enrichment is achieved. Under low-temperature alkaline-thermal conditions, the glassy phase of fly ash undergoes local depolymerization, and the Si-O-Al and Si-O-Si bonds are activated and broken. Calcium, silicon, and aluminum components are re-coordinated in the carrier channels and particle surfaces, forming AFt and C-(A)-SH nuclei in situ. This process does not involve the addition of cement clinker, strong alkaline solutions, or commercial seed crystals, maintaining the solid waste properties of the material system. Furthermore, after treatment, the activator is no longer merely a component providing alkalinity, but forms a composite active unit with functions of alkaline slow release, nucleus induction, and interfacial reaction. This significantly improves the utilization efficiency of effective components in solid waste, shortens the early induction period of the phosphogypsum-based cementing system, promotes AFt skeleton overlap and C-(A)-SH gel filling and bonding, and enhances the early strength, interfacial density, and volume stability of the high-dosage phosphogypsum system.
[0025] (4) The present invention employs CO2 micro-carbonization nucleation treatment, which, by controlling the intensity of CO2 action, causes free CaO, Ca(OH)2 and soluble Ca² to be released on the surface of the particles. + The process preferentially generates nano-CaCO3 and restricts CO2 diffusion into the particle interior, thus forming a reaction interface of "surface nano-carbonate nucleation sites - internal alkali-retaining active core". The surface nano-CaCO3 can serve as a heterogeneous nucleation template, inducing rapid deposition and growth of AFt and C-(A)-SH at the particle interface; while the incompletely carbonized alkaline components inside continuously release OH-. - and Ca² + This technology maintains the alkaline environment required for subsequent sulfate activation and potentially active silicon-aluminum reactions. It transforms unstable components such as free CaO into fine-scale stable nuclei, reducing the risk of expansion, while retaining the continuous activation ability of the activator. This achieves a synergistic effect of surface-level nucleation, internal continuous activation, and interface densification. Unlike traditional complete carbonization or ordinary CO2 curing processes, it can provide heterogeneous nucleation sites while retaining the ability for subsequent alkaline activation.
[0026] (5) This invention induces the refinement and ordered formation of ettringite through AFt crystal nuclei, promotes the rapid construction of gel networks through C-(A)-SH crystal nuclei, promotes the secondary growth of hydration products through nano-CaCO3 nucleation sites, and promotes the secondary growth of hydration products through Ca... 2+ It promotes the conversion of soluble phosphorus and fluorine into the low-solubility calcium-phosphorus phase and calcium-fluorine phase, thereby achieving a synergistic improvement in strength development, structural densification and environmental safety.
[0027] (6) Under standard curing conditions, the obtained solidified body has a 3-day compressive strength of 4-20 MPa, a 7-day compressive strength of 10-35 MPa, and a 28-day compressive strength of 30-70 MPa; when the phosphogypsum content is 75-80 parts, the 28-day compressive strength is 45-70 MPa; when the phosphogypsum content is 81-88 parts, the 28-day compressive strength is 30-50 MPa. It can be used in engineering scenarios such as mine filling, goaf filling, grouting reinforcement, roadbed backfilling, trench backfilling, foundation treatment, underground cavity filling and ecological backfilling of abandoned mine pits.
[0028] (7) The C-(A)-SH gel, AFt crystal, calcium phosphorus phase and calcium fluorine phase in the solidified body obtained by the present invention work together to reduce the risk of migration of phosphorus, fluorine and heavy metals, and are suitable for large-scale solid waste engineering utilization scenarios with requirements for environmental safety. Attached Figure Description
[0029] Figure 1 The present invention provides a process flow diagram for the preparation of high-dosage phosphogypsum-based cementitious materials derived from all-solid waste and excited by bicrystalline seed.
[0030] Figure 2 The microstructure and pore characteristics of Example 2 and comparative samples are shown in the figure (including X-ray diffraction, thermogravimetric analysis, scanning electron microscopy and mercury porosimetry results). Detailed Implementation
[0031] The following embodiments further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0032] The specific implementation provides a process flow for preparing a high-dosage phosphogypsum-based cementitious material derived entirely from solid waste and excited by bicrystalline seeding, as shown in the attached document. Figure 1 As shown. This includes temperature-controlled crystal-preserving drying of phosphogypsum, fractional-temperature-limited ultrafine grinding, alkaline-thermal reconstruction using fly ash-based porous carriers, low-temperature hydrothermal self-generated AFt / C-(A)-SH twin seeding, CO2 micro-carbonization nucleation, stepwise mixing of main materials, and curing and molding steps. The specific process is as follows: A specific embodiment provides a method for preparing a fly ash-based porous carrier: Fly ash, red mud, and carbide slag were mixed in a mass ratio of (40-70):(10-30):(10-30), and water was added to adjust the water-solid ratio to 0.35-0.80. The mixture was stirred and reacted at 50-95℃ for 2-12 h. Subsequently, the mixture was dried under controlled temperature, ultrafine ground, and air classified to obtain a fly ash-based porous carrier with D90≤10 μm.
[0033] In the alkaline-thermal reconstruction reaction, the Ca(OH)2 released from the carbide slag and the alkaline components in the red mud act together on the glassy phase of the fly ash, causing partial breakage of the Si-O-Si and Si-O-Al bonds on the surface of the fly ash, releasing active silicon-aluminum units, and reacting with Ca... 2+ Recombination occurs, forming a porous reconstructed body containing C-(A)-SH gel precursors, aluminosilicate gel precursors, and basic calcium-silica-alumina active sites. A micron-to-submicron composite pore structure is constructed by utilizing the packing pores between fly ash hollow microspheres, red mud flake particles, and carbide slag flocculent Ca(OH)2 particles, as well as the secondary pores formed by water evaporation and gel shrinkage during the alkaline-thermal reaction. The fly ash-based porous carrier is used to load AFt crystal nuclei, C-(A)-SH crystal nuclei, nano-CaCO3 nucleation sites, and basic calcium-silica-alumina active components, and plays a role in seed dispersion, alkaline slow release, silica-alumina compensation, and pore filling during the hydration process of high-dosage phosphogypsum-based cementitious materials.
[0034] Utilizing the aforementioned fly ash-based porous carrier, a specific embodiment also provides a method for preparing an all-solid waste-derived biogenic seed activator: (1) Preparation of pre-reaction slurry from all solid waste sources: 10-30 parts of aluminum ash or red mud with D90≤10 μm, 15-40 parts of waste glass powder or siliceous tailings powder, 20-45 parts of carbide slag, 10-25 parts of desulfurized gypsum or phosphogypsum fine powder, 5-20 parts of steel slag micro powder, and 5-20 parts of fly ash-based porous carrier are mixed by mass, and water is added and stirred to obtain pre-reaction slurry from all solid waste sources.
[0035] (2) Low-temperature hydrothermal self-generated twinning seed reaction: The pre-reaction slurry is heated and hydrothermally reacted at 40-95℃ for 2-24 hours to allow Ca, Si, Al and SO4 from the solid waste source to be separated. 2- A low-temperature pre-reaction occurs, generating AFt and C-(A)-SH crystal nuclei in situ, yielding a self-generated twin seed precursor; the low-temperature hydrothermal self-generated twin seed reaction includes the self-generation reaction of AFt and C-(A)-SH crystal nuclei; wherein, carbide slag provides Ca(OH)2 and Ca... 2+ Desulfurized gypsum or phosphogypsum powder provides SO4 2-Aluminum ash or red mud provides the Al source, waste glass powder or siliceous tailings powder provides the Si source, steel slag powder provides the active calcium-silicon phase and alkaline components, and fly ash-based porous carrier provides the porous loading space and slow-release sites for silicon and aluminum. The above components undergo a synergistic pre-reaction of solid waste source Ca-Si-Al-S under low-temperature hydrothermal conditions of 40-95℃, forming AFt crystal nuclei, C-(A)-SH crystal nuclei and alkaline calcium-silicon-aluminum active sites dispersed in situ in the pores and particle surfaces of fly ash-based porous carrier.
[0036] (3) Graded CO2 micro-carbonization nucleation treatment: The obtained self-generated twin seed precursor product is subjected to graded CO2 micro-carbonization nucleation treatment, and the carbonization degree is controlled to be 5-35% to obtain micro-carbonized self-generated twin seed precursor. The graded CO2 micro-carbonization nucleation treatment includes one or more combinations of atmospheric pressure CO2 micro-carbonization, pressurized CO2 micro-carbonization, or supercritical CO2 micro-carbonization. The atmospheric pressure CO2 micro-carbonization treatment conditions are: CO2 volume fraction 60-99%, treatment temperature 20-60℃, treatment time 60-180 min, and solid material moisture content 5-25%. The pressurized CO2 micro-carbonization treatment conditions are: CO2 pressure 0.2-7.0 MPa, treatment temperature 20-80℃, treatment time 30-120 min, and solid material moisture content 3-25%. The supercritical CO2 micro-carbonization treatment conditions are: CO2 pressure 7.5–20 MPa, treatment temperature 35–80℃, treatment time 5–90 min, and solid material moisture content 3–25%; preferably, CO2 pressure 8–15 MPa, treatment temperature 40–60℃, treatment time 5–45 min, and solid material moisture content 5–15%. The carbonization degree of the staged CO2 micro-carbonization nucleation treatment is controlled to be 5–35%, so that nano-CaCO3 nucleation sites are generated on the surface of the particles, while Ca(OH)2, free CaO, active calcium-silicon phase or alkaline calcium-silicon-aluminum phase are still retained inside the particles; the nano-CaCO3 nucleation sites are used to induce the uniform dispersion and secondary growth of AFt crystal nuclei and C-(A)-SH crystal nuclei, and the alkaline components retained inside are used to continuously stimulate the reaction of granulated blast furnace slag, fly ash and phosphogypsum.
[0037] (4) Powdering treatment of activator: The obtained micro-carbonized self-generated twin seed precursor is dried at 35-80℃ for 6-36 h, and then subjected to ultrafine grinding and air classification to obtain a solid waste self-generated twin seed activator with D90≤10 μm.
[0038] Specifically, the raw materials for the all-solid waste-derived bicrystalline seed activator are all subjected to temperature-controlled crystal-preserving drying, ultrafine grinding, and airflow classification treatment, with a D90 ≤ 10 μm. The desulfurized gypsum and phosphogypsum fine powder contain calcium sulfate dihydrate phase, and the drying temperature is controlled at 35–60℃, preferably 45–55℃, for 6–36 h to remove free water and surface adsorbed water, and to maintain the CaSO4·2H2O crystal phase structure from dehydration transformation. The aluminum ash, red mud, waste glass powder, siliceous tailings powder, carbide slag, steel slag micro powder, and fly ash-based porous carrier are dried at 35–80℃, preferably 50–70℃, for 6–36 h.
[0039] Based on this, a specific embodiment also provides a high-dosage phosphogypsum-based cementitious material. First, granulated blast furnace slag, fly ash, carbide slag, and a whole solid waste-derived bicrystalline seed activator with D90≤10μm are premixed for 3-10 min to uniformly disperse AFt crystal nuclei, C-(A)-SH crystal nuclei, nano-CaCO3 nucleation sites, and alkaline calcium-silica-alumina active components on the surface of silica-alumina solid waste and alkaline solid waste particles. Then, phosphogypsum with D90≤10 μm that maintains the CaSO4·2H2O crystal phase structure without dehydration transformation is added and mixed for 3-8 min. Finally, water is added and stirred for 3-8 min, with a water-cement ratio of 0.28-0.38, preferably 0.32.
[0040] Specifically, its composition by weight is as follows: 75-88 parts phosphogypsum, 6-18 parts granulated blast furnace slag, 2-8 parts fly ash, 3-8 parts calcium carbide slag, and 0.5-3.0 parts of self-generated twinning seed activator from all solid waste. Specifically, the phosphogypsum is subjected to temperature-controlled drying, ball milling or vibratory milling, and air classification, resulting in a D50 of 1–5 μm and a D90 ≤ 10 μm. The drying temperature of the phosphogypsum is 35–60℃, preferably 45–55℃, and the drying time is 6–36 h to maintain the CaSO4·2H2O crystal phase structure from dehydration and transformation.
[0041] Specifically, the granulated blast furnace slag and fly ash are subjected to graded temperature-controlled drying, followed by grinding in an air jet mill, vertical mill, stirred mill, or ball mill. After grading, the D50 is 2–6 μm, the D90 is ≤10 μm, and the specific surface area is 600–1200 m². 2 / kg. The drying temperature of the granulated blast furnace slag and fly ash is 50-90℃, preferably 60-80℃, and the drying time is 4-24 h.
[0042] Specifically, after being subjected to temperature-controlled drying, grinding, and grading, the calcium carbide slag has a D50 of 1–4 μm and a D90 ≤ 10 μm. The drying temperature of the calcium carbide slag is 45–80℃, preferably 50–70℃, and the drying time is 4–24 h, in order to reduce the moisture content and avoid significant carbonization or agglomeration and deactivation of Ca(OH)2.
[0043] In specific embodiments, the phosphogypsum, granulated blast furnace slag, fly ash, carbide slag, and all-solid waste-derived self-generated twin-crystal activator are all subjected to ultrafine grinding and classification treatment, with a powder particle size D90 ≤ 10 μm. The ultrafine grinding adopts a fractional temperature-limited ultrafine activation and airflow classification closed-loop circulation process. Among them, the material temperature during the grinding process of phosphogypsum containing calcium sulfate dihydrate, desulfurized gypsum, or phosphogypsum fine powder is controlled not higher than 60℃, preferably not higher than 55℃; the material temperature during the grinding process of carbide slag is controlled not higher than 80℃; granulated blast furnace slag, fly ash, steel slag micro powder, waste glass powder, or siliceous tailings powder are treated by airflow mill, vertical mill, ball mill, vibratory mill, or stirred mill to expose the glass phase, calcium-silicon phase, and silicon-aluminum active phase. The ultrafine grinding process includes primary crushing, secondary fine grinding, tertiary ultrafine grinding, and air classification. Primary crushing controls the material particle size to be ≤1 mm, secondary fine grinding controls the material D90 to be ≤45 μm, and tertiary ultrafine grinding and air classification control the material D90 to be ≤10 μm. During air classification, the classifying wheel frequency is 30–80 Hz, the induced draft frequency is 20–60 Hz, and through a closed-loop grinding-classification cycle and particle size detection feedback, the D90 of each powder is ensured to be no greater than 10 μm.
[0044] Example 1 This embodiment illustrates the preparation method of a fully organically generated twin seed activator derived from solid waste.
[0045] By weight, 20 parts red mud, 25 parts waste glass powder, 30 parts calcium carbide slag, 15 parts fine phosphogypsum powder, 10 parts steel slag powder, and 10 parts fly ash-based porous carrier were weighed. The fine phosphogypsum powder, a solid waste raw material containing calcium sulfate dihydrate, was first dried at 50℃ for 24 hours to remove free water and surface adsorbed water, and to maintain the CaSO4·2H2O crystal phase structure from dehydration transformation. The red mud, waste glass powder, calcium carbide slag, steel slag powder, and fly ash-based porous carrier were each dried at 60℃ for 24 hours. After drying, each raw material underwent primary crushing, secondary fine grinding, tertiary ultrafine grinding, and air classification to control D90 ≤ 10 μm.
[0046] A fly ash-based porous carrier was prepared by the following method: fly ash, red mud, and carbide slag were mixed in a mass ratio of 60:20:20, and water was added to adjust the water-to-solid ratio to 0.50. The mixture was stirred and reacted at 80℃ for 8 h, allowing the Ca(OH)2 released from the carbide slag and the alkaline components in the red mud to synergistically act on the glassy phase of the fly ash. This caused partial breakage of the Si-O-Si and Si-O-Al bonds on the surface of the fly ash, releasing active silicon-aluminum units, which then reacted with Ca... 2+The reconstituted material was reorganized to form a porous reconstructed body containing C-(A)-SH gel precursor, aluminosilicate gel precursor, and basic calcium silicate aluminum active sites. Subsequently, it was dried at a controlled temperature of 60℃ for 12 h, and then subjected to ultrafine grinding and air classification to obtain a fly ash-based porous carrier with D90≤10 μm.
[0047] The above-mentioned red mud, waste glass powder, carbide slag, phosphogypsum fine powder, steel slag micro powder, and fly ash-based porous carrier were mixed, water was added and stirred, and the water-to-solid ratio was controlled at 0.45 to obtain a pre-reacted slurry from all solid waste sources. This slurry was then subjected to a low-temperature hydrothermal reaction at 75℃ for 10 h to allow the Ca, Si, Al, and SO4 from the solid waste sources to react. 2- A synergistic pre-reaction occurs, generating AFt and C-(A)-SH crystal nuclei in situ.
[0048] Subsequently, the precursor obtained from the hydrothermal reaction was subjected to pressurized CO2 micro-carbonization treatment at a CO2 pressure of 2.0 MPa, a treatment temperature of 50℃, and a treatment time of 60 min. The moisture content of the solid material was controlled at 12%, and the degree of carbonization was controlled at approximately 18%. This process generates nano-CaCO3 nucleation sites on the surface of the precursor particles, while retaining Ca(OH)2, free CaO, active calcium-silicon phase, and alkaline calcium-silicon-aluminum phase inside.
[0049] The micro-carbonized precursor was dried at 60℃ for 12 h under controlled temperature, followed by ultrafine grinding and air classification to obtain a fully solid waste-derived bicrystalline seed activator with a D90 ≤ 10 μm. The activator obtained in this embodiment has the following technical characteristics: a fly ash-based porous carrier provides seed loading space and slow-release sites for silicon and aluminum; low-temperature hydrothermal reaction generates AFt and C-(A)-SH crystal nuclei in situ; CO2 micro-carbonization constructs nano-CaCO3 nucleation sites on the particle surface, while retaining alkaline activating components internally. This activator can play a role in seed induction, heterogeneous nucleation, alkaline slow release, and silicon-aluminum compensation in subsequent high-dosage phosphogypsum-based cementitious materials.
[0050] Comparative Example 1 This comparative example prepared a basic high-dosage phosphogypsum-based cementitious material without self-generated twinning activator, serving as a basic reference for illustrating the strengthening system of this invention. By weight, 75 parts phosphogypsum, 15 parts granulated blast furnace slag, 5 parts fly ash, 5 parts carbide slag, and 32 parts water were weighed. The phosphogypsum and carbide slag were dried at 60℃ for 24 h, followed by ball milling for 30 min; the granulated blast furnace slag and fly ash were dried at 60℃ for 24 h and treated using an air jet mill with a classifier wheel frequency of 50 Hz and an induced draft fan frequency of 30 Hz. After weighing and thoroughly mixing the raw materials according to the proportions, water was added at a water-cement ratio of 0.32 and stirred to obtain a homogeneous slurry. The slurry was poured into a 20 mm × 20 mm × 20 mm cubic mold, compacted, covered with a film for moisture retention, demolded, and cured according to standard conditions, and then the compressive strength was tested.
[0051] This comparative example did not include any self-generated twin seed activator derived entirely from solid waste, nor did it introduce low-temperature hydrothermal self-generated AFt / C-(A)-SH twin seeds or CO2 micro-carbonization nucleation sites. The resulting solidified body exhibited a 7-day compressive strength of 11.11 MPa and a 28-day compressive strength of 49.16 MPa. These results indicate that the phosphogypsum-slag-fly ash-carbide slag basic system can achieve a certain strength under appropriate grinding and alkaline activation conditions, but there is still room for further improvement in early reaction efficiency, seed induction ability, and structural control ability of the high-dosage phosphogypsum system.
[0052] Example 2 This embodiment prepared a self-generated twinned seed reinforced high-strength cementitious material to illustrate the strengthening effect after introducing a fully solid waste-derived self-generated twinned seed activator into the basic proportion of Comparative Example 1. By mass, 75 parts of phosphogypsum, 15 parts of granulated blast furnace slag, 5 parts of fly ash, 5 parts of carbide slag, 1.2 parts of the fully solid waste-derived self-generated twinned seed activator prepared in Example 1, and 32 parts of water were weighed.
[0053] The raw material pretreatment is as follows: phosphogypsum is dried at 50℃ for 24 h under controlled temperature and crystal preservation conditions. After ball milling and air classification, the D50 is 1–5 μm, and the D90 is ≤10 μm, while maintaining the CaSO4·2H2O crystal phase structure without dehydration and transformation. Granulated blast furnace slag and fly ash are dried at 70℃ for 12 h. After air milling and classification, the D50 is 2–6 μm, the D90 is ≤10 μm, and the specific surface area is 800–1000 m². 2 / kg; after drying the carbide slag at 60℃ for 12 h, and after low-temperature grinding and classification, the D50 is 1~4 μm and the D90≤10 μm. The material temperature during the grinding process is controlled not to exceed 70℃ in order to avoid obvious carbonization or agglomeration and deactivation of Ca(OH)2.
[0054] In preparation, granulated blast furnace slag, fly ash, carbide slag, and a self-generated twin-crystal activator derived from solid waste were first added to a mixer and premixed for 5 minutes to ensure that AFt nuclei, C-(A)-SH nuclei, nano-CaCO3 nucleation sites, and alkaline calcium-silica-alumina active components were uniformly dispersed on the surface of silica-alumina solid waste and alkaline solid waste particles. Then, phosphogypsum was added and mixing continued for 5 minutes. Finally, water was added and stirred for 5 minutes to obtain a uniform slurry. The slurry was poured into a 20 mm × 20 mm × 20 mm mold, compacted, covered with a film to retain moisture, and demolded after 24 hours. It was then cured under standard curing conditions of 20 ± 2℃ and 95 ± 1% relative humidity.
[0055] Based on the measured strength of 49.16 MPa at 28 days in Comparative Example 1, this embodiment improves early reaction efficiency and later structural compactness through ultrafine activation with D90≤10 μm, induction by self-generated AFt / C-(A)-SH twin seed, and heterogeneous nucleation of nano-CaCO3. The resulting solidified body has a 3-day compressive strength of 8.6 MPa, a 7-day compressive strength of 18.4 MPa, and a 28-day compressive strength of 56.8 MPa. Compared with Comparative Example 1, the introduction of a fully solid waste-derived self-generated twin seed activator improved both early strength and 28-day strength, indicating that AFt nuclei, C-(A)-SH nuclei, and nano-CaCO3 nucleation sites can shorten the reaction induction period and promote the uniform generation of hydration products and the compaction of the pore structure.
[0056] This embodiment is applicable to scenarios that require both early and late strength, such as grouting reinforcement, high-strength mine backfilling, and foundation treatment.
[0057] Example 3 This embodiment illustrates the preparation method of a high-absorption cementitious material with a phosphogypsum content of 83 parts. By mass, 83 parts of phosphogypsum, 9 parts of granulated blast furnace slag, 3 parts of fly ash, 5 parts of carbide slag, 1.5 parts of the all-solid waste-derived bicrystalline seed activator prepared in Example 1, and 34 parts of water are weighed.
[0058] All solid waste raw materials were subjected to temperature-controlled drying, ultrafine grinding, and airflow classification according to the method described in Example 2, with D90 ≤ 10 μm. Specifically, the drying temperature of phosphogypsum was controlled at 50℃ to prevent the CaSO4·2H2O crystal phase structure from dehydrating and transforming; the material temperature during the grinding process of carbide slag was controlled not to exceed 70℃ to maintain the alkaline release capacity of Ca(OH)2.
[0059] In preparation, granulated blast furnace slag, fly ash, carbide slag, and a fully solid waste-derived twin-crystal activator are premixed for 6 minutes, then phosphogypsum is added and mixed for 5 minutes, and finally water is added and stirred for 5 minutes to obtain a homogeneous slurry. After pouring, compacting, covering with a film for moisture retention, and standard curing, a solidified body of high-content phosphogypsum-based cementitious material is obtained.
[0060] The resulting solidified body exhibited a 3-day compressive strength of 5.7 MPa, a 7-day compressive strength of 13.8 MPa, and a 28-day compressive strength of 39.6 MPa. These results indicate that when the phosphogypsum content was increased to 83 parts, the amounts of slag and fly ash in the system decreased, and the number of silicon-aluminum reaction units decreased. However, the all-solid waste-derived bicrystalline seed activator could still maintain good strength development through seed induction, silicon-aluminum slow release, and alkaline compensation.
[0061] In this embodiment, the phosphogypsum content was increased to 83 parts, significantly enhancing the phosphogypsum absorption capacity of the material. While the relatively reduced content of slag and fly ash resulted in fewer silicon-aluminum reaction units in the system, the all-solid waste-derived biogenic twin seed activator provided AFt nuclei, C-(A)-SH nuclei, nano-CaCO3 nucleation sites, and alkaline calcium-silicon-aluminum active components, compensating for the insufficient release of silicon and aluminum in the high-phosphogypsum system. The fly ash-based porous carrier continued to release silicon-aluminum active units during hydration, playing a role in pore filling and seed dispersion, enabling the material to maintain good mechanical properties and volume stability even with high phosphogypsum content.
[0062] Example 4 This embodiment illustrates the preparation method of an ecological backfill cementitious material with an ultra-high dosage of 87 parts of phosphogypsum. By weight, 87 parts of phosphogypsum, 6 parts of granulated blast furnace slag, 2 parts of fly ash, 5 parts of carbide slag, 2.0 parts of a fully organically sourced twin-crystal activator from solid waste, and 36 parts of water are weighed.
[0063] The all-solid waste-derived bicrystalline seed activator is prepared using an atmospheric pressure CO2 micro-carbonization method. Specifically, 15 parts of aluminum ash, 30 parts of siliceous tailings powder, 30 parts of carbide slag, 15 parts of desulfurized gypsum, 10 parts of steel slag powder, and 10 parts of fly ash-based porous carrier are weighed. Each raw material undergoes temperature-controlled drying, ultrafine grinding, and airflow classification, with a D90 ≤ 10 μm. The drying temperature of the desulfurized gypsum is controlled at 50℃ to maintain the CaSO4·2H2O crystal phase structure without dehydration transformation. Water is added to the above raw materials and stirred to form a pre-reaction slurry. A low-temperature hydrothermal reaction is carried out at 85℃ for 8 h to generate AFt and C-(A)-SH crystal nuclei in situ. Subsequently, atmospheric pressure CO2 micro-carbonization treatment is performed with a CO2 volume fraction of 90%, a treatment temperature of 40℃, a treatment time of 120 min, a material moisture content of 15%, and a carbonization degree controlled to approximately 20%. After temperature-controlled drying, ultrafine grinding, and air classification, a fully solid waste-derived bicrystalline seed activator with D90≤10 μm was obtained.
[0064] When preparing the main cementitious material, granulated blast furnace slag, fly ash, carbide slag and the above-mentioned activator are premixed for 8 minutes, then phosphogypsum is added and mixed for 6 minutes, and finally water is added and stirred for 6 minutes, then shaped and cured.
[0065] The resulting solidified body exhibited a 3-day compressive strength of 4.2 MPa, a 7-day compressive strength of 10.5 MPa, and a 28-day compressive strength of 31.8 MPa. These results demonstrate that even with an ultra-high phosphogypsum content of 87 parts, the material can still achieve strength levels suitable for ecological backfilling, underground cavity filling, and general backfill reinforcement through self-generated twin seed activation and CO2 micro-carbonization nucleation treatment.
[0066] In this embodiment, the phosphogypsum content reaches 87 parts, mainly targeting the scenarios of large-scale phosphogypsum disposal and ecological backfilling. Although the slag and fly ash content is low, the activator contains self-generated AFt / C-(A)-SH twin seeds and nano-CaCO3 nucleation sites, which can promote the uniform generation of hydration products between the phosphogypsum skeleton; the Ca²⁺ released by carbide slag, steel slag powder and micro-carbonization precursors + It can react with soluble phosphorus and fluorine in phosphogypsum to form low-solubility calcium-phosphorus and calcium-fluorine phases, thereby reducing the risk of migration of pollutants. This embodiment is applicable to scenarios such as ecological backfilling of abandoned mine pits, filling of low-intensity mined-out areas, remediation of solid waste dumps, and ecological restoration of land space.
[0067] Comparative Example 2 This comparative example uses a common solid waste activator system without low-temperature hydrothermal pre-reaction to illustrate the role of low-temperature hydrothermal self-generated twinning reaction. According to the cementitious material ratio of Example 2, 75 parts of phosphogypsum, 15 parts of granulated blast furnace slag, 5 parts of fly ash, 5 parts of carbide slag, 1.2 parts of activator, and 32 parts of water were weighed. The raw material composition of the activator was the same as in Example 1, namely 20 parts of red mud, 25 parts of waste glass powder, 30 parts of carbide slag, 15 parts of fine phosphogypsum powder, 10 parts of steel slag powder, and 10 parts of fly ash-based porous carrier; however, each raw material was only dried, ultra-finely ground, and mixed, without undergoing a 75℃ low-temperature hydrothermal pre-reaction, and without pre-generating AFt and C-(A)-SH crystal nuclei. After preparation, molding, and curing according to the same method as in Example 2, the resulting solidified body had a 3-day compressive strength of 5.1 MPa, a 7-day compressive strength of 13.2 MPa, and a 28-day compressive strength of 50.4 MPa. Compared with Example 2, the early strength and 28-day strength of this comparative example were both reduced, indicating that relying solely on the compounding of solid waste powder is insufficient to fully exert the seed induction effect. Low-temperature hydrothermal pre-reaction to generate AFt crystal nuclei and C-(A)-SH crystal nuclei is an important measure to improve the reaction efficiency and structural densification of the high-dosage phosphogypsum system.
[0068] Comparative Example 3 This comparative example uses a self-generated twin-crystal activator system without CO2 micro-carbonization nucleation treatment to illustrate the role of CO2 micro-carbonization nucleation treatment. A pre-reaction slurry from a solid waste source was prepared according to the method in Example 1 and subjected to a low-temperature hydrothermal reaction at 75°C for 10 h to generate AFt and C-(A)-SH crystal nuclei in situ. However, the hydrothermal reaction product was not subjected to CO2 micro-carbonization treatment and was directly dried at 60°C for 12 h. After ultrafine grinding and airflow classification, the un-micro-carbonized self-generated twin-crystal activator was obtained.
[0069] The cementitious material was prepared according to the formulation of Example 2 and cured using standard methods. The resulting cured body had a 3-day compressive strength of 6.4 MPa, a 7-day compressive strength of 15.6 MPa, and a 28-day compressive strength of 52.1 MPa. Compared with Example 2, the strength of this comparative example is lower than that of the system treated with CO2 micro-carbonization nucleation, indicating that the surface nano-CaCO3 nucleation sites can promote the secondary growth of AFt and C-(A)-SH hydration products, improving the uniformity of seed dispersion and the density of the later structure.
[0070] Comparative Example 4 This comparative example uses an activator system subjected to excessive CO2 carbonization treatment to illustrate the necessity of controlling the degree of CO2 micro-carbonization. A low-temperature hydrothermal self-generated twin seed precursor was prepared according to the method in Example 1, followed by pressurized CO2 carbonization treatment at a CO2 pressure of 2.0 MPa, a treatment temperature of 50°C, and a treatment time extended to 240 min. The moisture content of the solid material was controlled at 12%, increasing the degree of carbonization to approximately 55%. After temperature-controlled drying, ultrafine grinding, and airflow classification, the excessive carbonization activator was obtained.
[0071] The cementitious material was prepared according to the proportions in Example 2 and cured using standard methods. The resulting solidified body had a 3-day compressive strength of 4.8 MPa, a 7-day compressive strength of 12.1 MPa, and a 28-day compressive strength of 47.6 MPa. Compared with Example 2, the strength decreased significantly after excessive carbonization, indicating that when the Ca(OH)2, free CaO, and active calcium-silicon phase inside the carbide slag, steel slag powder, or activator precursor are excessively consumed, the subsequent alkaline activation capacity of the system decreases, which is not conducive to the continuous reaction of slag, fly ash, and phosphogypsum. Therefore, this invention limits CO2 treatment to a micro-carbonization nucleation process with a carbonization degree of 5-35%, rather than a complete carbonation process.
[0072] Comparative Example 5 This comparative example uses an untreated phosphogypsum system to illustrate the effect of temperature-controlled crystal-preserving drying of phosphogypsum. The components were weighed according to the proportions in Example 2. The phosphogypsum was dried at 105°C for 12 hours before grinding. The remaining raw materials and the all-solid-waste-derived seed activator were treated according to Example 2. X-ray diffraction analysis showed that the characteristic peak of CaSO4·2H2O in the phosphogypsum dried at 105°C was weakened, and some characteristics of hemihydrate or anhydrous gypsum were observed.
[0073] After preparation, molding, and curing using the same method as in Example 2, the resulting cured body exhibited a 3-day compressive strength of 6.2 MPa, a 7-day compressive strength of 14.3 MPa, and a 28-day compressive strength of 49.8 MPa. Compared to Example 2, the lack of temperature-controlled crystal preservation treatment led to a decrease in the stability of the sulfate release process and the AFt formation process, indicating that controlling the drying temperature of phosphogypsum at 35–60°C, preferably 45–55°C, is necessary to maintain the CaSO4·2H2O crystal phase structure and achieve the ordered formation of AFt.
[0074] Example 5 This embodiment illustrates the composition of hydration products, CO2 micro-carbonization alkali retention characteristics, and pore structure densification in the material of the present invention. Solidified samples from Examples 2, 2, 3, and 4 after 28 days of curing were subjected to anhydrous ethanol to terminate hydration, low-temperature drying, and grinding. X-ray diffraction, scanning electron microscopy, and mercury porosimetry were then performed. Simultaneously, thermogravimetric analysis and DTG comparison analysis were conducted on Examples 2 and 4 to verify the effects of micro-carbonization and over-carbonization treatments on CaCO3 formation and Ca(OH)2 retention. Results are shown in the appendix. Figure 2 .
[0075] X-ray diffraction results showed that characteristic peaks of AFt, CaCO3 and unreacted CaSO4·2H2O could be observed in the sample of Example 2, while C-(A)-SH gel existed in the form of weak crystals or diffuse peaks. Compared with Comparative Example 2, the characteristic peak of AFt in Example 2 was more obvious, indicating that the AFt crystal nuclei formed by the low-temperature hydrothermal pre-reaction can promote the subsequent formation of ettringite.
[0076] Thermogravimetric analysis results showed that the sample of Example 2 contained a CaCO3 decomposition weight loss region, while a Ca(OH)2 related weight loss signal could still be detected, indicating that the CO2 micro-carbonization treatment formed calcium carbonate nucleation sites, but did not completely consume the internal alkaline components. In Comparative Example 4, the CaCO3 content was significantly increased while the Ca(OH)2 signal was weakened, indicating that excessive carbonization would weaken the subsequent alkaline activation ability.
[0077] Scanning electron microscopy results showed that the needle-like AFt crystals in the sample of Example 2 were more uniformly distributed, and the C-(A)-SH gel was continuously filled between the particles, resulting in a relatively dense pore structure. In Comparative Example 2, the hydration products were unevenly distributed, with more local pores. The gel filling degree in Comparative Example 3 was lower than that in Example 2. In Comparative Example 4, more carbonate particles were observed to accumulate, and the gel continuity was insufficient.
[0078] Mercury intrusion porosimetry results showed that the sample of Example 2 had a lower total porosity and a higher proportion of fine pore structure than the comparative sample, indicating that the synergistic effect of self-generated twin seeds and CO2 micro-carbonization nucleation can promote pore refinement and structural densification.
[0079] Example 6 This embodiment illustrates the volume stability and water stability of the high-dosage phosphogypsum-based cementitious material of the present invention. Slurries prepared in Examples 2, 3, 4, and Comparative Example 1 were molded into standard specimens and cured at 20±2℃ and a relative humidity of not less than 95%. The linear expansion rate after 28 days, the compressive strength retention rate after immersion in water for 7 days, and the compressive strength retention rate after 5 wet-dry cycles were tested.
[0080] Test results show that: Example 2 cured body had a linear expansion rate of 0.06% after 28 days, a strength retention rate of 91% after immersion in water for 7 days, and a strength retention rate of 86% after 5 wet-dry cycles; Example 3 cured body had a linear expansion rate of 0.08% after 28 days, a strength retention rate of 87% after immersion in water for 7 days, and a strength retention rate of 82% after 5 wet-dry cycles; Example 4 cured body had a linear expansion rate of 0.10% after 28 days, a strength retention rate of 83% after immersion in water for 7 days, and a strength retention rate of 78% after 5 wet-dry cycles.
[0081] Comparative Example 1, due to the absence of a fully organic twin-seed activator derived from solid waste, exhibited insufficient uniformity in AFt formation and gel filling, resulting in lower strength retention after immersion and wet-dry cycles compared to Example 2. These results demonstrate that the present invention, through AFt nucleus-induced ettringite refinement, continuous C-(A)-SH gel filling, and the promotion of uniform growth of hydration products via nano-CaCO3 nucleation sites, can improve the volume stability and water stability of high-dosage phosphogypsum-based cementitious materials.
[0082] Example 7 This embodiment illustrates the preparation of a reinforced activator and cementing material using supercritical CO2 micro-carbonization. By weight, 20 parts red mud, 25 parts waste glass powder, 30 parts calcium carbide slag, 15 parts phosphogypsum fine powder, 10 parts steel slag micro powder, and 10 parts fly ash-based porous carrier were weighed. All raw materials underwent temperature-controlled drying, ultrafine grinding, and airflow classification, with a D90 ≤ 10 μm.
[0083] The above powders were mixed and then water was added and stirred, with a water-to-solid ratio of 0.45, to obtain a pre-reacted slurry from all solid waste sources. The slurry was placed under low-temperature hydrothermal reaction at 80℃ for 10 h to allow the Ca, Si, Al, and SO4 from the solid waste sources to react. 2- A synergistic pre-reaction occurs, forming AFt crystal nuclei, C-(A)-SH crystal nuclei, and alkaline calcium-silicon-aluminum active sites dispersed in the pores and particle surfaces of the fly ash-based porous carrier.
[0084] The obtained precursor was placed in a supercritical CO2 reactor, with the CO2 pressure controlled at 10 MPa, the processing temperature at 45℃, the processing time at 30 min, the material moisture content at 10%, and the carbonization degree at approximately 15%. Under these conditions, supercritical CO2 entered the pores between precursor particles and the porous carrier channels, forming uniformly distributed nano-CaCO3 nucleation sites on the surface of carbide slag and steel slag, while Ca(OH)2, free CaO, and active calcium-silicon phases were retained inside the particles.
[0085] The micro-carbonized product was dried at 60℃ for 12 h, and then subjected to ultrafine grinding and air classification to obtain a supercritical CO2 micro-carbonization enhanced all-solid waste-derived bicrystalline seed activator with D90≤10 μm.
[0086] High-strength cementitious materials were prepared using this activator: 75 parts of phosphogypsum, 15 parts of granulated blast furnace slag, 5 parts of fly ash, 5 parts of carbide slag, 1.0 part of supercritical CO2 micro-carbonization strengthening activator, and 32 parts of water were weighed by weight. The preparation, molding, and curing methods were the same as in Example 3.
[0087] The resulting cured body exhibited a 3-day compressive strength of 7–13 MPa, a 7-day compressive strength of 16–25 MPa, and a 28-day compressive strength of 55–65 MPa. These results indicate that supercritical CO2 micro-carbonization can be considered one of the preferred enhancement methods for the CO2 micro-carbonization nucleation treatment of this invention, used to improve the uniformity of nano-CaCO3 nucleation sites in the porous carrier channels and particle surfaces. However, this invention does not require supercritical CO2 treatment as a necessary condition.
[0088] In this embodiment, supercritical CO2 mainly improves the uniformity of nano-CaCO3 nucleation sites in the channels and particle surfaces, without pursuing complete carbonization.
[0089] To further illustrate the effects of low-temperature hydrothermal self-generated twin seed reaction, CO2 micro-carbonization nucleation treatment, CO2 micro-carbonization degree control, and phosphogypsum temperature-controlled crystal preservation treatment on the performance of high-dosage phosphogypsum-based cementitious materials, the main preparation methods and compressive strength results of Examples 2, 3, 4, and Comparative Examples 1-5 were compared, and the results are shown in Table 1.
[0090] Table 1
[0091] As can be seen from Comparative Examples 2-5, low-temperature hydrothermal pre-reaction, CO2 micro-carbonization nucleation, micro-carbonization degree control, and temperature-controlled crystal preservation of phosphogypsum are not conventional process steps that can be arbitrarily omitted, but rather key technical characteristics that jointly determine the early reaction efficiency, later strength, and structural stability of the high-dosage phosphogypsum system. Table 1 shows that low-temperature hydrothermal pre-reaction, CO2 micro-carbonization nucleation treatment, micro-carbonization degree control, and temperature-controlled crystal preservation of phosphogypsum all have a significant impact on the development of material strength. Specifically, low-temperature hydrothermal pre-reaction can pre-form AFt and C-(A)-SH crystal nuclei, improving the early seed induction effect; CO2 micro-carbonization nucleation treatment can form nano-CaCO3 heterogeneous nucleation sites on the particle surface, promoting secondary growth of hydration products and pore filling; controlling the carbonization degree to 5-35% can retain internal alkaline components while forming surface nucleation sites, avoiding excessive carbonization that leads to a decrease in subsequent excitation capacity; temperature-controlled crystal preservation of phosphogypsum helps maintain the CaSO4·2H2O crystal phase structure, promoting stable sulfate release and orderly AFt formation. The above results show that the present invention is not a simple solid waste compound, but improves the early reaction efficiency and later structural densification degree of high-dosage phosphogypsum-based cementitious materials through the synergistic regulation of "temperature control and crystal preservation of phosphogypsum - induction of self-generated twin crystal seeds - CO2 micro-carbonization nucleation - internal alkali preservation and continuous excitation".
[0092] Example 8 This embodiment illustrates the stabilizing effect of the high-dosage phosphogypsum-based cementitious material of the present invention on phosphorus, fluorine, and heavy metals. Unprocessed phosphogypsum and the solidified bodies obtained in Comparative Example 1, Example 2, Example 3, and Example 4 were used as test objects. After being crushed to a specified particle size, leaching tests were conducted to detect the F content in the leachate. - PO4 3- And the concentrations of heavy metal ions such as Cu, Pb, Cd, Ni, As, and Hg.
[0093] F in the leachate of undisturbed phosphogypsum - The concentration was 137.315 mg / L, PO4 3- The concentration was 213.897 mg / L. After curing the base system of Comparative Example 1, F - The concentration decreased to 2.173 mg / L, PO4 3- The concentration decreased to 0.207 mg / L.
[0094] In Example 2, due to the introduction of a fully solid waste-derived bicrystalline seed activator, nano-CaCO3 nucleation sites, and a fly ash-based porous carrier, the C-(A)-SH gel, AFt crystals, and calcium phosphorus / calcium fluoride stable phase in the solidified body were further increased. The F content in the solidified body obtained in Example 2 was also increased. - The leaching concentration is 2–5 mg / L, PO4 3-The leaching concentration was 0.1–0.5 mg / L; the F in the cured body obtained in Example 3 - The leaching concentration is 3–8 mg / L, PO4 3- The leaching concentration was 0.2–0.8 mg / L; the F in the cured body obtained in Example 4 - The leaching concentration is 4–9 mg / L, PO4 3- The leaching concentration was 0.3–1.0 mg / L. The leaching concentrations of heavy metal ions such as Cu, Pb, Cd, Ni, As, and Hg were all lower than the limits required for relevant engineering applications or solid waste resource utilization, indicating that the system has a synergistic stabilizing effect on phosphorus, fluorine, and heavy metals.
[0095] Its stabilization mechanism lies in the release of Ca from calcium carbide slag and steel slag powder. 2+ It can react with soluble phosphate and fluoride ions to form a low-solubility calcium-phosphate phase and CaF2; C-(A)-SH gel can reduce the migration of heavy metals through physical adsorption, ion exchange, and pore encapsulation; AFt crystals can exhibit solid solution, adsorption, and structural encapsulation effects on some anions and metal ions; fly ash-based porous carriers further provide pore adsorption and slow-release stabilizing space. Therefore, the high-dosage phosphogypsum-based cementitious material prepared by this invention not only has high strength but also good environmental safety.
[0096] Example 9 This embodiment illustrates the application of the material of the present invention in mine backfilling and grouting reinforcement. A high-absorption phosphogypsum-based cementitious material slurry was prepared using the proportions described in Example 3. During on-site construction, phosphogypsum with a D90 ≤ 10 μm, granulated blast furnace slag, fly ash, carbide slag, and a fully solid waste-derived self-generated twin-crystal activator were stored separately in sealed silos and proportionally transported to a continuous mixing device via a metering system. First, the granulated blast furnace slag, fly ash, carbide slag, and activator were added and dry-mixed, then phosphogypsum was added and mixed, and finally water was added and continuously stirred to form a slurry. The slurry was then pumped to the goaf, grouting hole, or backfill area via a pumping system.
[0097] During construction, the slurry exhibits good pumpability and filling properties. After curing, the phosphogypsum skeleton in the material provides volume support, AFt crystals fill the pores and form an early skeleton, C-(A)-SH gel is continuously generated in the pores and provides later bonding strength, and nano-CaCO3 nucleation sites promote the uniform growth of hydration products. According to the strength results of the standard-cured neat slurry specimens in Example 3, the 28-day compressive strength of the material can reach 39.6 MPa. When used for on-site mine filling, grouting reinforcement, roadbed backfilling, or ecological backfilling, the water-cement ratio and slurry consistency can be appropriately adjusted according to the pumping distance, construction moisture content, filling space conditions, and on-site curing environment. The on-site core sampling strength is usually lower than the strength of the standard-cured neat slurry specimens, but it can still meet the engineering application requirements of mine filling, grouting reinforcement, roadbed backfilling, and ecological backfilling through mix optimization.
[0098] The above embodiments collectively demonstrate that this invention is not a simple conventional compounding of phosphogypsum, slag, fly ash, and carbide slag, nor is it ordinary CO2 carbonization solid waste treatment. Instead, it employs a continuous technical route of "temperature-controlled crystal preservation of phosphogypsum – fractional temperature-limited ultrafine activation – fly ash-based porous carrier loading – low-temperature hydrothermal self-generated AFt / C-(A)-SH twin seed crystals – CO2 micro-carbonization surface nucleation and internal alkali retention – high-dosage phosphogypsum solidification and molding." This route achieves synergistic control of sulfate release, silica-alumina dissolution, seed crystal induction, gel bonding, pore refinement, and phosphorus-fluorine stability in a high-dosage phosphogypsum system. This technical route can improve the phosphogypsum utilization ratio, early reaction efficiency, later strength, volume stability, and environmental safety while maintaining the overall solid waste properties. It can be widely applied in large-scale engineering applications such as mine backfilling, grouting reinforcement, roadbed backfilling, trench backfilling, and ecological backfilling.
Claims
1. A high-content phosphogypsum-based cementitious material for solid waste, characterized in that... The composition by weight is as follows: 75-88 parts phosphogypsum, 6-18 parts granulated blast furnace slag, 2-8 parts fly ash, 3-8 parts calcium carbide slag, and 0.5-3.0 parts of whole solid waste-derived twin seed activator; The water-cement ratio should be controlled between 0.28 and 0.
38.
2. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 1, characterized in that... The phosphogypsum is dried under controlled temperature and volume, pulverized by ball milling or vibration milling, and then subjected to air classification. The resulting D50 is 1–5 μm and the D90 is ≤10 μm.
3. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 1, characterized in that... The granulated blast furnace slag and fly ash are subjected to graded and temperature-controlled drying, followed by grinding in an air jet mill, vertical mill, stirred mill, or ball mill. After classification, the D50 is 2–6 μm, the D90 is ≤10 μm, and the specific surface area is 600–1200 m². 2 / kg.
4. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 1, characterized in that... After being processed by temperature-controlled drying, grinding, and grading, the carbide slag has a D50 of 1–4 μm and a D90 ≤ 10 μm.
5. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 1, characterized in that... The preparation method of the all-solid-waste-derived bicrystalline seed activator includes the following steps: (1) Preparation of pre-reaction slurry from all solid waste sources: 10-30 parts of aluminum ash or red mud with D90≤10 μm, 15-40 parts of waste glass powder or siliceous tailings powder, 20-45 parts of carbide slag, 10-25 parts of desulfurized gypsum or phosphogypsum fine powder, 5-20 parts of steel slag micro powder, and 5-20 parts of fly ash-based porous carrier are mixed by mass, and water is added and stirred to obtain pre-reaction slurry from all solid waste sources; (2) Low-temperature hydrothermal self-generated twinning reaction: The pre-reaction slurry is heated and hydrothermally reacted at 40-95℃ for 2-24 h to allow Ca, Si, Al and SO4 from the solid waste source to be separated. 2- A low-temperature pre-reaction occurs, generating AFt crystal nuclei and C-(A)-SH crystal nuclei in situ, thus obtaining a self-generated twin seed precursor; (3) Graded CO2 micro-carbonization nucleation treatment: The obtained self-generated twin seed precursor product is subjected to graded CO2 micro-carbonization nucleation treatment, and the degree of carbonization is controlled to be 5-35% to obtain micro-carbonized self-generated twin seed precursor. (4) Powdering treatment of activator: The obtained micro-carbonized self-generated twin seed precursor is dried at 35-80℃ for 6-36 h, and then subjected to ultrafine grinding and air classification to obtain a solid waste self-generated twin seed activator with D90≤10 μm.
6. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 5, characterized in that... The graded CO2 micro-carbonization nucleation process employs one or more combinations of atmospheric pressure CO2 micro-carbonization, pressurized CO2 micro-carbonization, and supercritical CO2 micro-carbonization.
7. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 6, characterized in that... The atmospheric pressure CO2 micro-carbonization treatment conditions are: CO2 volume fraction 60-99%, treatment temperature 20-60℃, treatment time 60-180 min, and solid material moisture content 5-25%.
8. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 6, characterized in that... The pressurized CO2 microcarbonation treatment conditions are: CO2 pressure 0.2–7.0 MPa, treatment temperature 20–80℃, treatment time 30–120 min, and solid material moisture content 3–25%.
9. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 6, characterized in that... The supercritical CO2 microcarbonation treatment conditions are: CO2 pressure 7.5-20 MPa, treatment temperature 35-80℃, treatment time 5-90 min, and solid material moisture content 3-25%.
10. The high-content phosphogypsum-based cementitious material for solid waste as described in claim 5, characterized in that... The preparation method of the fly ash-based porous carrier includes the following steps: Fly ash, red mud, and carbide slag were mixed in a mass ratio of (40-70):(10-30):(10-30), and water was added to adjust the water-solid ratio to 0.35-0.
80. The mixture was stirred and reacted at 50-95℃ for 2-12 h. Subsequently, the mixture was dried under controlled temperature, ultrafine ground, and air classified to obtain a fly ash-based porous carrier with D90≤10 μm.
11. The method for preparing the high-content phosphogypsum-based cementitious material for solid waste according to any one of claims 1-10, characterized in that... Includes the following steps: First, granulated blast furnace slag, fly ash, carbide slag and whole solid waste-derived twin seed activator are premixed for 3-10 minutes, then phosphogypsum is added and mixed for 3-8 minutes, and finally water is added and stirred for 3-8 minutes. The mixture is then poured, pumped, grouted or filled into shape, and cured to obtain a solidified body of high-content phosphogypsum-based cementitious material.
Citation Information
Patent Citations
Method for mineralizing and fixing carbon dioxide by using strengthened steel slag
CN103111186B
Optimization Method for Proportioning of Phosphopyrogypsum-Based All-Solid Waste Backfill Material to Improve Top-Level Filling Ratio
CN110723952B
A method for preparing a highly water-resistant anhydrous phosphogypsum cementitious material
CN111978061B
A method for preparing a modified phosphogypsum-based reinforced and toughened cementitious material
CN114149187B
Solid waste-based lightweight aggregate based on charcoal internal carbonization and preparation method of solid waste-based lightweight aggregate
CN114538850A